The Values of Tauhid Education in Rejang’s Culture of Serambeak - Fakhruddin Fakhruddin (STAI Hubbulwathan Duri, 2021)
This study aims to reveal and formulate the values of Tauhid education in Serambeak, the local culture of Rejang community. The culture of Serambeak has been a system for the continuation of Islamic education since Islam came and entered the life of Rejang community. The content of Tauhid educational values in Serambeak culture is the spark of the Rejang community's needs. To reveal the main points of this study, the researcher used qualitative methods with a descriptive-analytic approach to collect, analyse, and interpret to produce valid research. The findings concluded the following: First, the values of Tauhid education in Serambeak are an effort to accommodate Islamic education to local culture, demonstrating a good acculturation process of local culture. Second, by using Serambeak as a local culture with its literary beauty, the Rejang community is more likely to accept the values of Tauhid education brought by Islam as a foreign religion. Third, the Serambeak culture's values of Tauhid education state that God, Tauhid affirmation, God's power, God's perfection, the creator of the universe, and the nature of divinity as the cultivation of good and actual Tauhid teachings. Fourth, the values of Tauhid education are an attempt to erode and erase the beliefs of animism and dynamism that have been so strong and rooted in the life of the Rejang people. They are very effectively changed using the arguments of belief.